The Effect of Applying Predict, Organize, Rehearse, Practice, Evaluate (PORPE) Strategy on Students’ Reading Comprehension - Dewi Sinaga; Berlin Sibarani (Universitas Negeri Medan, 2013)
ABSTRACTThis study was conducted as an attempt to find out the effect of applying Predict, Organize, Rehearse, Practice, Evaluate (PORPE) strategy on students’ reading comprehension. This study used experimental design. The population of this study was students of Grade XI, Senior High School (Sekolah Menengah Atas: SMA) Negeri 1 Lumbanjulu which consisted of 120 students. There were sixty students from the population taken as the sample in this study. The sample was divided into two randomized groups: experimental and control groups. The experimental group was taught by using PORPE strategy, while the control group was taught by using conventional method.To obtain the reliability of the test, the writer applied Kuder Richardson 21 formula (KR-21). The result of the reliability was 0.81. The data were analyzed by using t-test formula. The analysis showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significance 0.05 with the degree of freedom (df) 58 , t-observed value 2.8 > t-table value 2.00. The findings indicated that using PORPE strategy significantly affected the students’ reading comprehension. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.Keywords: PORPE Strategy, Reading Comprehension